Hybrid Energy System Modelling for Oil & Gas Fields: A Case Study of Pasakhi Satellite Oil & Gas Complex - Mustafa, Fahim; Ali Sahito, Anwar; Ahmed Khatri, Shoaib; Kumar, Laveet (Distributed Generation & Alternative Energy Journal, 2021)
Energy is needed for all community activities, the production of all goods, and the provision of all services. It is extremely important to a country’s economy and wealth. Currently, conventional fossil fuels provide most of the world’s energy. In case of oil and gas fields their energy consumption is totally off-grid, their generation depends upon fossil fuels, the cost of energy consumption of oil and gas fields are too high because operational work of the field is totally depending upon fossil fuels. The development of off-grid renewable energy generation technologies offers the opportunity for tackling these challenges. This study provides a techno-economic feasibility analysis of an off-grid hybrid renewable energy system [HRES] for Pasakhi Satellite Oil & Gas Field, Tando Jam, Hyderabad, Sindh, Pakistan. The proposed hybrid energy system designed for field consists of the different combination of solar Photovoltaics [PVs], wind turbines, batteries, and generator to meet the required energy consumption demand. The renewable hybrid energy system is model and optimized configuration through powerful simulation software Hybrid Optimized Model for Electric Renewable [HOMER] Pro. The optimized configuration of the hybrid system consists of solar PV’s (50 kW), Wind turbines (60 kW), 40 lead-acid batteries (165 Ah and 12V each), 30 kw generator and 100 kW converter. The simulation results show that the proposed system can meet the power requirements of 250 kWh/day primary demand load with 40.21 kW peak load. This system configuration has the Capital Cost $71040, the Net Present Cost [NPC] of $253,159 and Cost of Energy [COE] of 0.215$/kWh. Furthermore, the results of the present study are compared with the literature because of which a cost-effective HRES with a low COE has been established.